Loss analysis and efficiency enhancing method for a unipolar hysteresis‐Controlled single‐phase grid‐connected inverter. Issue 8 (16th April 2018) - Haruna, Junnosuke; Masubuchi, Nobuhiro; Iwase, Shintaro; Funato, Hirohito
Abstract : This paper compares control schemes using hysteresis control and a conventional triangle‐carrier comparison control to discuss the theoretical efficiency of a grid‐connected inverter. Control schemes for the gird‐connected inverter are actively studied to improve the efficiency and performance of the system. Hysteresis controls are one of the solutions to satisfy these issues. However, the theoretical efficiency under the same performance using conventional carrier comparison method has not been discussed. This paper considers the performance of unipolar and bipolar hysteresis control compared with unipolar and bipolar carrier comparison methods by theoretical calculations, simulations, and experimental results. As a result, we find that unipolar hysteresis control can improve the efficiency of the inverter. © 2018 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.